Environmental conditions and possibility of self-control in epileptic seizures of Chilean schoolchildren - Luzoro, J.; Vergara, V. (Revista de Psicología, 1997)
In search of complementary or alternative treatments, a questionnaire-interview was applied to 50 epileptic schoolchildren refractory to drug therapy, whose ages ranged from 7 to 14 years. Their mothers were also interviewed. The questionnaire was intended to specify the environmental conditions and the possible possibilities of self-control of the convulsive crises. Among the results, we found the most relevant to be that 76% of the crises occur at home, 68% in the presence of family members, 26% of children identify signs prior to the crises and 24% say they manage to avoid them. These results support the view that psychological support consisting of identifying pre-seizure conditions and behaviors may eventually make them less likely.